THE ROLE OF ACADEMIC TUTORING AND EMOTION REGULATION IN MITIGATING LEARNING BOREDOM AMONG STUDENTS AT SMA KHAIRUNNAS GUNUNG ANYAR SURABAYA - Derisma VIta Noviyanti; Didit Darmawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to examine the effect of tutoring and emotion regulation on learning saturation of Khairunnas Gunung Anyar Surabaya high school students. Learning burnout becomes a serious obstacle in achieving students' academic and developmental goals. This study is to analyze the causes of students' learning saturation. The results showed that tutoring services have a positive and significant influence in reducing students' learning saturation. Tutoring not only provides academic benefits but also helps students psychologically overcome boredom during learning. A structured tutoring program, with support from the principal, teachers, and guardians, is able to create a conducive educational environment. Emotion regulation has also been shown to play an important role in reducing boredom. Students with high levels of emotion regulation are better able to identify factors that cause boredom and take steps to overcome them. An in-depth understanding of emotion regulation can be the basis for designing effective educational interventions. Therefore, teachers need to pay attention to variations in learning methods, provide adequate support and guidance, and provide constructive feedback. Keywords: Tutoring; Emotion Regulation; Learning Boredom; Khairunnas Gunung Anyar Surabaya High School Students.